General banking activities of Islami Bank Bangladesh Ltd - Saaqib, Md. Sobaed-Bin-Mahbub (BRAC University, 2018)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2018.